2020
DOI: 10.4236/gep.2020.81001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Toxicity Potential of Sedimentary PAHS from Refome Lake, South-East Nigeria over the Last Century

Abstract: In this study, toxic equivalent factors and sediment quality guidelines were employed for the assessment of toxicity potential of PAHs in 2 sediment cores collected from the center (RC) and shoreline (RS) of Reforme lake, SE Nigeria over the last ~1 century. Boundary cross plots of isomeric ratios such as Ant/Ant + Phe (>0.1) vs. Fl/Fl + Pyr (>0.4) and BaA/BaA + Chry (>0.35) vs. Icdp/Icdp + Bper (>0.2) indicated biomass combustion/domestic coal utilization as the main sources of PAHs input. The result revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Studies have shown that indiscriminate disposals of petroleum products into the environment have led to increment in the heavy metals concentrations in the soils, waters bodies and their sediments. Oyo-Ita et al [12] reported that sediments collected within the vicinity of crude oil spill sites contain significant amount of heavy metals [12]. Chukwujindu [10] stated that bioavailability and toxicity of heavy metals are influenced by the various forms and amount bound to the sediment matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that indiscriminate disposals of petroleum products into the environment have led to increment in the heavy metals concentrations in the soils, waters bodies and their sediments. Oyo-Ita et al [12] reported that sediments collected within the vicinity of crude oil spill sites contain significant amount of heavy metals [12]. Chukwujindu [10] stated that bioavailability and toxicity of heavy metals are influenced by the various forms and amount bound to the sediment matrices.…”
Section: Introductionmentioning
confidence: 99%